CONDUCTING THE FIRST STAGE OF TRAINING WITH FOOTBALL PLAYERS THROUGH ACTION GAMES IN THE EDUCATIONAL AND LEARNING PROCESS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article considers the problems of monitoring and analyzing the physical activity of football players during the initial stages of physical training. The volume and intensity of football players' movements during the game are determined.